S69 Serum osteoprotegerin predicts mortality in a prospective study on incident cases of pulmonary arterial hypertension. (2nd December 2011) - Condliffe, R; Pickworth, J; Hopkinson, K; Hameed, A; Walker, S; Elliot, C; Francis, S; Newman, C; Crossman, D; Morton, A; Kiely, D; Lawrie, A
Abstract : Background and Objectives: Despite improvements in the overall management of Pulmonary Arterial Hypertension (PAH) the disorder still causes significant morbidity and mortality. Current treatments fail to reverse the disease, and clinical assessment does not always differentiate between, or reflect, the local pathogenesis within the heart or pulmonary circulation. Current proposed biomarkers, for example, brain natriuretic peptide (BNP and NT-proBNP), largely reflects myocardial rather than pulmonary vascular remodelling. Subsequently, there has been increasing interest in identifying a biomarker for PAH that can track with lung pathology, and treatment. Through our desire to understand disease pathogenesis, our studies in vitro and in animal models have identified osteoprotegerin (OPG) as a candidate biomarker. We have previously reported that OPG was elevated in a prevalent cohort of patients with IPAH. The aim of this study was to verify the utility of OPG as a biomarker for PAH in a second cohort of incident cases and assess the effect of treatment at follow-up visits. Methods: Serum samples were obtained from 35 patients with IPAH, 26 patients with CTD-PAH and 65 age-matched controls. Serum OPG concentrations were measured by ELISA, correlations with pulmonary haemodynamics, routine clinical biochemistry and prognostic significance were then assessed. Results: OPG concentrations were significantly elevated in IPAH (mean 4485 pg/ml) and CTD-PAH (3824 pg/ml) compared to controls (1749 pg/ml). Concentrations of OPG correlated positively with pulmonary vascular resistance (PVR) and WHO functional class and negatively with the incremental shuttle walk test (ISWT). An OPG concentration above 4744 pg/ml predicted poorer survival. OPG was significantly lower in patients at follow-up after the commencement of targeted PAH therapies. Conclusion: PAH is characterised by elevated serum OPG and this correlates with functional class and PVR. Perhaps most importantly high serum levels of OPG predict a poor outcome. Further longitudinal work is required, and is currently underway to further validate these findings.